The Diagnostic Efficacy of Urine Cytology in Screening Bladder Cancers: A Retrospective Study - Shanthi, Vissa; Rao, B.Shyam Sundara; Rao, C.Nandam Mohan; Grandhi, D. Bhavana; Reddy, E.Vangala Chidananda; Sreesailam, F.Swathi (International Journal of Medical Research and Review, 2015)
Background: Exfoliative urine cytology is considered to be an essential non-invasive procedure for the diagnosis of bladder cancers and also for monitoring the patients with bladder cancers. Objective: The present study was carried out to determine the efficacy of urinary cytology in detecting the bladder cancer by analyzing the cytological findings in histopathologically proven bladder cancer patients. Methods: Urine cytology findings in 56 patients, who were histopathologically diagnosed to have bladder cancer were analyzed retrospectively. Urine specimen was centrifuged and sediment was examined for tumor cells. Results: Out of 56 patients studied, 28 patients showed malignant cells in urine (50%), 6 patients (10.71%) showed suspicious cells, 3 patients (5.36%) showed dysplastic cells and 19 patients (33.93%) urine cytology was negative for malignant cells. Urine cytology for malignant cells was positive in most cases having high grade bladder tumors and in tumors in advanced stage showing muscle infiltration. Conclusion: Urinary cytology is a less expensive, non-invasive procedure used for screening bladder tumors and can detect the high grade tumors and tumors with higher staging effectively.